2022
DOI: 10.1017/s104795112200258x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cardiac graft rejection on semilunar valve function: implications for heart valve transplantation

Abstract: Background: The treatment of neonates with unrepairable heart valve dysfunction remains an unsolved problem because there are no growing heart valve replacements. Heart valve transplantation is a potential approach to deliver growing heart valve replacements. Therefore, we retrospectively analysed the semilunar valve function of orthotopic heart transplants during rejection episodes. Methods: We included children who underwent orthotopic heart transplantation at our institution and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Immunosuppression for partial heart transplants is based on immunosuppression for pediatric heart transplants, because the valves contained in pediatric heart transplants are known to grow . It can be less stringent because the valves in heart transplants are spared from rejection . The long-term risks from immunosuppression are predictable based on the experience with pediatric heart transplants.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppression for partial heart transplants is based on immunosuppression for pediatric heart transplants, because the valves contained in pediatric heart transplants are known to grow . It can be less stringent because the valves in heart transplants are spared from rejection . The long-term risks from immunosuppression are predictable based on the experience with pediatric heart transplants.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in favor of this conclusion includes the observation that the valves in rejected OHTs retain their functional and structural integrity even after failure of the graft as a whole. 8,[31][32][33] Other studies on the cellular level demonstrated decreased or no antigenicity of the aortic valve when compared with the cardiac endothelium. 34,35 In a study of transplanted porcine hearts, Chen et al showed that while the donor heart is rejected due to IgM antibodies against the galactose α-1,3-galactose antigen that is strongly expressed on the cardiac endothelium, this antigen was not present on porcine aortic or pulmonary valves.…”
Section: Partial Heart Transplantationmentioning
confidence: 99%
“…Firstly, heart valves appear to enjoy a degree of immune privilege 84,85 . For example, the outflow valves of orthotopic heart transplants are histologically 12,36 and functionally 86 spared from rejection. Secondly, the risk from an immune response to a partial heart transplant is far less than the risk of an orthotopic heart transplant.…”
Section: Future Directions In Laboratory Investigationsmentioning
confidence: 99%